Modern Refrigeration and Air Conditioning - Althouse, Andrew D. (GoodHeart-Willcox, 1996)
It provides the foundation on which a solid, thorough knowledge of refrigeration and air conditioning may be based. It also provides an excellent basis of information for you in the areas of servicing and troubleshooting.